Chaotic Desynchronization as the Therapeutic Mechanism of Deep Brain Stimulation - Wilson, Charles J.; Beverlin, Bryce; Netoff, Theoden I. (Frontiers in Systems Neuroscience, 2011)
High frequency deep-brain stimulation of the subthalamic nucleus (DBS) relieves many of the symptoms of Parkinson's disease in humans and animal models. Although the treatment has seen widespread use, its therapeutic mechanism remains paradoxical. The subthalamic nucleus is excitatory, so its stimulation at rates higher than its normal firing rate should worsen the disease by increasing subthalamic excitation of the globus pallidus. The therapeutic effectiveness of DBS is also frequency and intensity sensitive, and the stimulation must be periodic; aperiodic stimulation at the same mean rate is ineffective. These requirements are not adequately explained by existing models, whether based on firing rate changes or on reduced bursting. Here we report modeling studies suggesting that high frequency periodic excitation of the subthalamic nucleus may act by desynchronizing the firing of neurons in the globus pallidus, rather than by changing the firing rate or pattern of individual cells. Globus pallidus neurons are normally desynchronized, but their activity becomes correlated in Parkinson's disease. Periodic stimulation may induce chaotic desynchronization by interacting with the intrinsic oscillatory mechanism of globus pallidus neurons. Our modeling results suggest a mechanism of action of deep brain stimulation and a pathophysiology of Parkinsonism in which synchrony, rather than firing rate, is the critical pathological feature.